Synthesis of biogas supply networks using various biomass and manure types. (4th March 2019) - Egieya, Jafaru Musa; Čuček, Lidija; Zirngast, Klavdija; Isafiade, Adeniyi Jide; Pahor, Bojan; Kravanja, Zdravko
Highlights: Economic optimization model and application to biogas supply network is presented. Biogas supply network from various optional feedstocks is optimized. Poultry manure, poultry bedding and corn silage are optimal raw materials. Most profitable solution shows 13% dry matter and 59.44% methane content. Sensitivity analysis includes variations in prices, dry matter content and production of food. Abstract: This contribution presents a developed generic mixed integer linear programming (MILP) model for optimizing biogas supply network to generate electricity over monthly time-periods by maximizing the economic performance. Dry matter content and methane yield for each feedstock are included, which more accurately represents a realistic network. The model is applied to an illustrative case study of an agricultural biogas production plant in Slovenia. Optimal results show poultry manure and bedding and corn silage as the selected feedstocks to meet the production of 999 kW of electricity. Technologies selected include anaerobic digester, press-based dewatering and combined heat and power plant (CHP), while water, and heat required for the anaerobic digestion plant itself are "recycled". A profit after tax of about 254, 625 $/y is obtained. Furthermore, sensitivity analysis in terms of prices of electricity and digestate, dry matter content and utilization of crop residues is performed. Graphical abstract: Image, graphical abstract